Απλή μέθοδος εκτίμησης του φαινομένου της ξηρασίας με τη χρήση του δορυφορικού δείκτη NDVI - Πέτρου, Κατερίνα (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Drought is one of the major natural hazards, which affecting the environment and the economy of countries all around the globe. Reliance on meteorological data is not enough by itself in order to study areas of drought, especially when such data may be sparse and incomplete. By increasing the weather data through satellite images, we can determine the location and severity of drought. In this paper, we present the use of the satellite vegetation index NDVI (Normalized Difference Vegetation Index) for the study of drought between 2000 -2015 in Cyprus. The study was conducted with a series of satellite images each month (January-December) for 14 years (2000-2014), of the receiver Terra Modis on Cyprus, in particular for the study areas. The acquisition and data preparation entirely based on GIS environment (ArcMap 10.2.2), and processed in the application of Excel. Specifically in ArcMap were executed the image processing MODIS, digitization seven (7) agricultural study areas of Cyprus and the export NDVI mean values of each region. Mean values (MEAN) obtained with the use of the tool Zonal Statistics of ArcGIS, which calculates the average of the cells belonging to the same study area of each image. In Excel appropriate calculations were executed, the creation of charts and the export of results. The confirmation of the results was made using as a reference the data from the Meteorological Service. The index were identify the drought with the data of the Meteorological Office and highlighted the areas with the most intense phenomena during the period 2000 - 2014.
Keywords: Drought; Terra Modis; NDVI; Satellite vegetation index; Normalized difference vegetation index; Cyprus; Ξηρασία; Δείκτες ξηρασίας; Δορυφορικός δείκτης βλάστησης; Κύπρος